2018
DOI: 10.1016/j.oceaneng.2018.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PANS and LES of the flow past a generic ship

Abstract: The prediction of flow past a generic ship has been performed using partially-averaged Navier-Stokes (PANS) turbulence model. The Reynolds number based on the width of the ship is × 8 10 4. A detailed comparison with resolved large-eddy simulation (LES) solution and available experimental data is made for a better understanding of the capability of PANS in predicting the turbulent flow in the wake. The results show that PANS produces similar trends to those predicted by LES. However, a coarse grid resolution w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Flow state II (shown by dashed black lines) is transposed to compare directly with flow state I (continuous black lines), and these are compared with the data at identical locations from the numerical study of Syms (2008) (indicated by the continuous blue line) using Lattice-Boltzmann method (LBM), and the experimental data from Aerodynamics Laboratory of the National Research Council, Canada (NRC) at Re ¼ 5:59 Â 10 5 are indicated by the continuous red lines. Despite the larger Reynolds number in the latter study as compared to that of Zhang et al (2018), the flow asymmetry on the top step is well-predicted at the two streamwise locations, further indicating that the bi-stables states are observed at realistic Reynolds numbers, where ships and other bluff bodies operate.…”
Section: Methodology and Validationmentioning
confidence: 64%
See 4 more Smart Citations
“…Flow state II (shown by dashed black lines) is transposed to compare directly with flow state I (continuous black lines), and these are compared with the data at identical locations from the numerical study of Syms (2008) (indicated by the continuous blue line) using Lattice-Boltzmann method (LBM), and the experimental data from Aerodynamics Laboratory of the National Research Council, Canada (NRC) at Re ¼ 5:59 Â 10 5 are indicated by the continuous red lines. Despite the larger Reynolds number in the latter study as compared to that of Zhang et al (2018), the flow asymmetry on the top step is well-predicted at the two streamwise locations, further indicating that the bi-stables states are observed at realistic Reynolds numbers, where ships and other bluff bodies operate.…”
Section: Methodology and Validationmentioning
confidence: 64%
“…The length of the recirculation bubble is uniform across AE0:2W of the vertical midplane as seen in Fig. 16 of Zhang et al (2018), and does not vary significantly from that computed in the vertical midplane. The recirculation lengths, X R1 and X R2 in flow state II are approximately 6% and 3.2% longer as compared to flow state I.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations